Urinary phoretograms performed by capillary electrophoresis in dogs with chronic disease with or without Leishmania infantum infection - Navarro, Paula Fátima; Fernández-Barredo, Salceda; Gil, Laura (Frontiers in Veterinary Science, 2022)
The study of early markers to detect renal dysfunction has increased in recent years, since serum markers such as creatinine increase when there is a 75% loss of renal mass. Urinary capillary electrophoresis is an available laboratory technique that can provide an easily interpretable electrophoretic pattern divided into 5 fractions as in sera (fraction 1 corresponding to albumin; fraction 2 corresponding to alpha1-globulins; fraction 3 corresponding to alpha2-globulins; fraction 4 corresponding to beta-globulins; fraction 5 corresponding to gamma globulins), which can be useful in the early diagnosis of the disease. In this study, urinary capillary electrophoresis was performed in dogs with azotemia and proteinuria due to chronic kidney disease or Leishmania infantum infection and compared with reference intervals of healthy dogs. Statistical analysis was performed using one-way ANOVA. In urine phoretograms fraction 2 was increased in dogs with chronic kidney disease (CKD) compared to the healthy population (G0) and Leishmania infantum-infected dogs. Fraction 3 was increased in dogs with CKD and dogs infected with Leishmania infantum compared to G0. Fraction 4 was found to be decreased in CKD dogs and Leishmania infantum-infected dogs compared to G0. Fraction 5 was higher in Leishmania infantum dogs compared to G0 and CKD dogs. No statistical relationship was found between the protein/creatinine ratio (UPC) and the different fractions of the urinary phoretogram in the study population. No statistical relationship was found between serum and urine fractions in the study population. Urinary capillary electrophoresis is a non-invasive technique that can potentially be used as part of the diagnosis and follow-up in dogs with kidney disease due to different pathologies.